Analysis of the Insertion Process in Crime News Theo Van Leeuwen's Critical Discourse Analysis Study - Aprilia Anggraini; Else Liliani (Britain International for Academic Research (BIAR) Publisher, 2023)
This study aims to analyze the use of Leeuwen's inclusion theory in crime news with the theme of murder in the Online Tribun News.Com news. Data collection was carried out in three stages (1) reading and understanding the discourse on the theme of murder in the news Online Tribun News.Com with the aim of obtaining a clear understanding of the contents of the discourse to be studied, (2) marking parts of the discourse related to the theory of inclusion. Leeuwen, and (3) record sentences in discourse related to Leeuwen's inclusive theory by using a data recording format. Data analysis was carried out descriptively. Based on the results of the study it can be concluded, Leeuwen's inclusioan theory found in ten criminal news headlines with the theme of murder in the Online Tribun News.Com news is five of the seven existing theories, namely objectivity-abstraction, nomination-categorization, nomination-identification, assimilation individualization and associations-dissociations. So, it can be concluded that writing criminal news with the theme of killing journalists does not marginalize victims. In making news headlines, journalists still hide actors. Concealment of actors by journalists is done by using passive sentences in news headlines.